2014
DOI: 10.1049/iet-map.2013.0161
|View full text |Cite
|
Sign up to set email alerts
|

Miniaturised printed slot antenna with multi‐ring technique for dual‐band and broadband operations

Abstract: Miniaturised microstrip‐line‐fed slot antennas with ring‐shaped metallic strips for dual‐band and broadband operations are investigated and verified in this study. The proposed designs implemented on a 0.8‐mm FR‐4 substrate show that the ring‐shaped metallic strips and the feeding structure yield multiple resonant modes, achieving 66.3% size reduction. The proposed dual‐band design reveals two operating bandwidths (12.4 and 46.5%) at the central frequencies of 2445 and 4813 MHz, respectively. The broadband des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…As observed from Figures , we can figure out that the operation bandwidth of the slotline antenna can be effectively enhanced without reshaping a thin slotline resonator into a wide aperture or complex geometry . Based on the above analysis, it is further found that the dual‐mode slotline radiator has a relatively high input impedance of 150–200 Ω, while its impedance bandwidth theoretically approaches 54.0% which is much larger than that of many conventional slot antennas.…”
Section: Principle and Analysesmentioning
confidence: 68%
See 1 more Smart Citation
“…As observed from Figures , we can figure out that the operation bandwidth of the slotline antenna can be effectively enhanced without reshaping a thin slotline resonator into a wide aperture or complex geometry . Based on the above analysis, it is further found that the dual‐mode slotline radiator has a relatively high input impedance of 150–200 Ω, while its impedance bandwidth theoretically approaches 54.0% which is much larger than that of many conventional slot antennas.…”
Section: Principle and Analysesmentioning
confidence: 68%
“…Table shows another aspect of comparison in terms of the LWR between the proposed and other reported antennas in . It is seen that the proposed slotline antenna is much narrow in slot width as highly demanded in design of slot antennas and its LWR is enlarged as up to 42.00.…”
Section: Design Test and Validationmentioning
confidence: 95%
“…Proceedings of ISAP 2014, Kaohsiung, Taiwan, Dec. [2][3][4][5]2014 resonant mode in the high-band, and makes the bandwidth improvement. A comprehensive analysis has been done to understand the effects of various dimensional parameters and to optimize the performances of the designed antennas [5].…”
Section: Fr2a_01 Fr2a_01 Fr2a_01 Fr2a_01mentioning
confidence: 99%
“…A comprehensive analysis has been done to understand the effects of various dimensional parameters and to optimize the performances of the designed antennas [5]. By properly selecting and tuning their dimensions (x 1 -4 ) of tuning stub to be an asymmetric shape (x 3…”
Section: Fr2a_01 Fr2a_01 Fr2a_01 Fr2a_01mentioning
confidence: 99%
“…SIW slot arrays [10] achieve multi-band performance in a straightforward manner, but suffer from narrowband characteristics and bulky footprints, as every additional band requires a separate antenna element with a footprint in the order of half a wavelength. Ring slot [11]- [12] or resonant slot [13]- [14] antennas exhibit bandwidth-limited behavior and low antenna/platform isolation, making close integration with active electronics virtually impossible. Conversely, cavity-backed slot antennas [15]- [18] exhibit excellent electromagnetic shielding capabilities, but generally rely on resonant slots, limiting the bandwidth.…”
Section: Introductionmentioning
confidence: 99%